PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS PENDEKATAN SAINTIFIK PADA MATERI SUHU DAN KALOR UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMP KELAS VII - Marza, Zarmega Marza Zarmega; Suryawati, Evi Suryawati Evi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to develop a Student Worksheet Scientific approach based on the material temperature and heat to improve critical thinking skills junior high school students of class VII at the designing aspect, pedagogical aspects, content aspect, indicator of the ability to think critically. This research was conducted from March to June 2015. This type of research is the development of research using ADDIE models. 3.7 KD research subjects understand the concept of temperature, thermal expansion, heat, heat transfer, and their application in the mechanism of safeguarding the stability of body temperature in humans and animals as well as in everyday life. The instrument used to collect data is LKS assessment sheets, sheets critical thinking skills and siswaData questionnaire responses obtained from LKS development based on a scientific approach to the material temperature and heat to improve critical thinking skills that have been validated by four (4) people valildator, comprising of Biology Education lecturer and science teacher at SMPN 1 Pekanbaru. Then validator gives the impression and suggest improvements to the worksheets that have been developed. After the results of the assessment worksheets revised based on suggestions and input from each validator. LKS subsequently revised junior high school students tested to Class VII. Student response data obtained from the test to the students of SMPN 1 Pekanbaru Class VII student of 20 people. Data critical thinking skills obtained through the assessment of answers to the critical thinking skills. LKS validation results from the design aspect is 3.25 with valid categories, namely pedagogic aspects of 3.33 with the category of very valid and aspects of content 3.08 with a valid category. Students' response to Aspect 94 with LKS is very good category. Results answer students' critical thinking skills, namely 77 with both categories.Keywords: Student Worksheet, Scientific approach and Critical thinking.